The effect of immunomodulator azoximer bromide on the cytokine profile in a complex therapy for children with newly diagnosed tuberculosis - Mironchuk, Yu. V.; Raznatovska, O. M. (Zaporozhye Medical Journal, 2022)
Aim. To analyze the effect of immunomodulator azoximer bromide on the serum cytokine profile (IL-2, IL-6, IL-4, IL-10) in the complex therapy for children with newly diagnosed tuberculosis (TB). Materials and methods. The study included 51 newly diagnosed TB children, who were divided into 2 groups: 26 children received immunomodulator azoximer bromide (main group) in combined therapy with concurrent antimycobacterial therapy (AMBT) and 25 children were assigned to only AMBT (control group). The main group children received azoximer bromide (immunomodulator) adjunctive therapy for immunological changes correction concurrently with the standard AMBT: children under the age of 10 years – orally 6 mg twice a day, children aged over 10 years – 12 mg twice a day; the treatment course – 14 days. The serum cytokine profile (IL-2, IL-6, IL-4, IL-10) was examined on the basis of the Immunological Department in the Training Medical and Laboratory Center of ZSMU by solid-phase enzyme-linked immunosorbent assay (ELISA) using a device ELISA – reader Sirio S with respective kits (Bender MedSystems GmbH, Austria, pcg/ml) before AMBT initiation and at the end of AMBT maintenance phase (MF). The study results were processed on a personal computer using the statistical package of the licensed program Statistica, version 13 (Copyright 1984–2018 TIBCO Software Inc. All rights reserved, License No. JPZ8041382130ARCN10-J). Results. At the AMBT initiation, newly diagnosed TB children of both groups showed a clear imbalance between pro- and anti-inflammatory cytokines towards pro-inflammatory ones with a predominance and high activity of Th1 type cellular immune response. The ratios of IL-2/IL-10 and IL-6/IL-10 pointed to the normalized balance in the regulatory system of pro- and anti-inflammatory cytokines in the main group children upon the MF of AMBT completion. The ratio of IL-2/IL-10 dropped 7.3-fold at the treatment completion relative to that at the initiation of treatment, however, compared to the control group at the end of treatment, it was 7.2 times less. The controls did not show significant on-treatment dynamics of the IL-2/IL-10 and IL-6/IL-10 ratios, the IL-2/IL-10 ratio was 12.8 times higher than in the healthy children group at the treatment completion. Conclusions. The use of immunomodulator azoximer bromide in combination therapy for newly diagnosed TB children helps to normalize all cytokine profiles and the balance in the regulatory system of pro- and anti-inflammatory cytokines after the AMBT completion. Therefore, the effect of immunomodulator azoximer bromide on the cytokine profile in the treatment for newly diagnosed TB children is substantial, which would increase the AMBT effectiveness among this patient group as a whole.